Predictive factors for disease recurrence in patients with locally advanced renal cell carcinoma treated with curative surgery. Issue 4 (31st March 2021) - Chang, Te-Wei; Cheng, Wei-Ming; Fan, Yu-Hua; Lin, Chih-Chieh; Lin, Tzu-Ping; Yi-Hsiu Huang, Eric; Chung, Hsiao-Jen; Huang, William J.S.; Weng, Shih-Han
Abstract : Background: Few prognostic factors have been proposed for patients with locally advanced renal cell carcinoma (RCC). This study aimed to investigate the possible predictive factors for disease-free survival (DFS) after curative surgery for RCC stage T3 or higher. Methods: Patients with locally advanced RCC who underwent cure-intended partial or radical nephrectomy, with or without tumor thrombectomy, at our institution from April 1, 2005 to October 31, 2013 were retrospectively reviewed. Those undergoing cytoreductive nephrectomy were excluded. Preoperative data, including surgical and pathologic characteristics, were assessed for correlation with DFS. Chi-square tests, univariate and multivariate Cox regression analysis, and Kaplan–Meier survival curve analyses were performed to determine potential predictive factors. A p value less than 0.05 was considered statistically significant. Results: A total of 159 patients were included for analysis. The mean duration of follow-up was 37.9 months, and 119 (74.8%) patients remained disease-free during follow-up. Disease recurrence was found in 40 (25.2%) patients, and pathologic T stage, capsule penetration, Fuhrman grade, thrombocytosis, renal vein thrombosis, and elevated serum alkaline phosphatase, platelet/lymphocyte ratio, and γ-glutamyl transpeptidase levels were significantly associated with disease recurrence on univariate analysis. On multivariate analysis, Fuhrman grade 3 or 4 (HR = 5.70, p = 0.0003, 95% CI = 2.23–14.56) showed significant associations with DFS. Conclusion: In patients with locally advanced RCC, Fuhrman grade was associated with worse DFS after curative surgery. Urologists should closely monitor patients with high Fuhrman grades.